The discovery of the genus Caecina Stal (Hemiptera: Reduviidae: Ectrichodiinae) from China, with the description of a new species - Cui, Jianxin; Li, Hu; Cai, Wanzhi (Zootaxa, 2008)
A species of the genus Caecina Stål has been discovered from China. Caecina sinica is described as new. Illustrations of habitus, phallus and other important characteristics of the new species are provided. The holotype is preserved in Entomological Museum of China Agricultural University.